“Estudio de factibilidad para la producción y comercialización de abonos orgánicos, para hortalizas en la ciudad de Loja” - Martínez Lalangui, Héctor David (2024)
Conventional agriculture requires chemical substances for plant nutrition and control of various pests and diseases that affect crops. These chemical substances are harmful to man and the environment, through the implementation of this project called “Feasibility study for the production and marketing of organic fertilizers for vegetables in the city of Loja", we present an alternative to improve the growing conditions of vegetables from various sectors, especially from the San Lucas, Chantaco and Taquil Parishes, where the largest number of producers and cultivation areas, through the production and marketing of organic fertilizers we contribute to the reduction of environmental pollution, offering a quality product that is friendly to the environment. During the research, surveys were applied with specific questions, the perception of the producers was determined. at the time of carrying out fertilization on their crops and if they would be willing to purchase organic fertilizers from the company if its implementation were to be implemented, it was determined that there is a future demand for 222,053 bags of organic fertilizers, and in the Loja market Currently, a quantity of 14,844 bags of organic fertilizer type bocashi and humus is offered, the study established that there is an unsatisfied demand for 207,209 bags of organic fertilizer in year one, and an investment of 18,624.05 is required to implement the project, the study determined a retail price per 35 kg bag of fertilizer for the first year of $3.32 dollars, obtaining a sales income of $79,680 dollars. These results indicate that it is feasible to launch the project. All financial indicators are positive and we maintain advantages in the market given that the public companies of the Municipality and Prefecture that are dedicated to the commercialization of this type of organic fertilizers do not cover the unsatisfied demand of the productive sector.